2020
DOI: 10.1039/d0ta09235e
|View full text |Cite
|
Sign up to set email alerts
|

High-performance Na–CO2batteries with ZnCo2O4@CNT as the cathode catalyst

Abstract: Rechargeable Na–CO2 batteries are promising energy storage devices for not only providing high energy density but also utilizing earth-abundant Na and greenhouse gas CO2. However, the Na–CO2 battery development deterred...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…The high-resolution XPS spectra of C 1s in discharged and charged MoS 2 /SnS 2 catalyst electrodes are shown in Figure c. The discharge product confirmed that the peak at 289.1 eV was attributed to Na 2 CO 3 that emerged in the discharged electrode . The other peaks such as metal carbide (283.5 eV), primary carbon (284.6 eV), C–O (285.9 eV), CO (286.7 eV), and carboxyl (288.4 eV) were seen in the discharged and charged MoS 2 /SnS 2 XPS results .…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The high-resolution XPS spectra of C 1s in discharged and charged MoS 2 /SnS 2 catalyst electrodes are shown in Figure c. The discharge product confirmed that the peak at 289.1 eV was attributed to Na 2 CO 3 that emerged in the discharged electrode . The other peaks such as metal carbide (283.5 eV), primary carbon (284.6 eV), C–O (285.9 eV), CO (286.7 eV), and carboxyl (288.4 eV) were seen in the discharged and charged MoS 2 /SnS 2 XPS results .…”
Section: Resultsmentioning
confidence: 79%
“…The discharge product confirmed that the peak at 289.1 eV was attributed to Na 2 CO 3 that emerged in the discharged electrode. 50 The other peaks such as metal carbide (283.5 eV), primary carbon (284.6 eV), C−O (285.9 eV), CO (286.7 eV), and carboxyl (288.4 eV) were seen in the discharged and charged MoS 2 /SnS 2 XPS results. 51 However, in the high-resolution XPS of C 1s in the charged electrode, the peak of Na 2 CO 3 vanished after the charging, as shown in Figure 3d.…”
Section: Resultsmentioning
confidence: 96%
“…The catalytic ability of the Ru/CNT cathode to decompose discharge products of Li–CO 2 and Na–CO 2 batteries to evolve CO 2 gas could be further verified using the in situ gas chromatography–mass spectrometry (GC–MS) characterization during the charging process. The detailed procedure and the utilization of homemade cell for GC–MS characterization have been discussed in the earlier reports. ,, Before the GC–MS measurement, predischarged electrodes of Ru/CNT were prepared using the cutoff capacity of 500 mAh g –1 at 100 mA g –1 . The predischarged Ru/CNT electrodes were utilized to assemble the homemade GC–MS cell and the charging process was performed simultaneously to monitor the evolution of CO 2 , O 2 , and decomposed electrolyte fragments in Li–CO 2 and Na–CO 2 batteries.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed procedure and the utilization of homemade cell for GC−MS characterization have been discussed in the earlier reports. 24,27,28 Before the GC−MS measurement, predischarged electrodes of Ru/ CNT were prepared using the cutoff capacity of 500 mAh g −1 at 100 mA g −1 . The predischarged Ru/CNT electrodes were utilized to assemble the homemade GC−MS cell and the charging process was performed simultaneously to monitor the evolution of CO 2 , O 2 , and decomposed electrolyte fragments in Li−CO 2 and Na−CO 2 batteries.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation